The Effect of Tunneling Incentive to Transfer Pricing Decision with Tax Minimization As a Moderating Variable - Suryarini, Trisni; Mega Cahyaningrum, Adhilia; Hidayah, Retnoningroum (KnE Social Sciences, 2020)
The aims of this research are to examine and to find empirical evidence about the effect of tunneling incentive to company decision of doing transfer pricing with tax minimization as a moderating variable. This study uses 145 manufacturing companies which listed in Indonesia Stock Exchange in 2012-2017 as the research population. Selection of sample in this study used purposive sampling method, and obtained 19 companies with 95 units analysis. Data analysis methods that used in this study are descriptive statistics analysis and inferential statistics analysis with absolute difference test in that moderated regression analysis. The result of this research indicates that tunneling incentive has positive and not significant effect to transfer pricing decision. Meanwhile, tax minimization significantly moderates the effect of tunneling incentive to transfer pricing. The conclusions of this research are tunneling incentive cannot determine the decision of transfer pricing in companies, then tax minimization can strengthen the relationship between tunneling incentive to transfer pricing decision. Keywords: Transfer Pricing; Tunneling Incentive; Tax Minimization.